1995
DOI: 10.21273/jashs.120.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Labeled Sodium (22Na+) Uptake and Translocation in Rabbiteye Blueberry Exposed to Sodium Chloride and Supplemental Calcium

Abstract: `Tifblue' rabbiteye blueberry (Vaccinium ashei Reade) plants grown in complete nutrient solution were supplied with 25 mm NaCl and with either 0, 3, or 10 mm supplemental Ca2+ added as a mixture of the sulfate, nitrate, and chloride salts. Uptake and partitioning of 22Na+ into leaves, stems, and roots from labeled nutrient solutions and subsequent translocation in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Accumulation of Na and Cl in plant tissues under salinity has been associated with osmotic adaptation (Heuer and Nadler, 1998;Pardossi et al, 1999) and improvement of water status in Vaccinium ashei Rehd. (Wright et al, 1995) and Pistacia spp. (Picchioni and Miyamoto, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…Accumulation of Na and Cl in plant tissues under salinity has been associated with osmotic adaptation (Heuer and Nadler, 1998;Pardossi et al, 1999) and improvement of water status in Vaccinium ashei Rehd. (Wright et al, 1995) and Pistacia spp. (Picchioni and Miyamoto, 1990).…”
Section: Resultsmentioning
confidence: 98%
“…The addition of Ca 2+ ameliorates the adverse effects of salinity on plants Martínez-Ballesta et al, 2000), although it has been reported that the addition of Ca 2+ has no effect on the salt tolerance of some lettuce genotypes (Cramer and Spurr, 1986). In blueberry plants treated with high NaCl levels, high Ca 2+ concentrations may even be harmful (Wright et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the addition of Ca 2+ ameliorates the adverse effects of salinity on plants Martínez-Ballesta et al, 2000). However it has been reported that Ca 2+ addition has no effects on the salt tolerance of some lettuce genotypes (Cramer and Spurr 1986), and in blueberry plants treated with high NaCl levels, high Ca 2+ concentrations are even harmful (Wright et al 1995).…”
Section: Introductionmentioning
confidence: 99%